A prospective cohort study of anterior cruciate ligament injuries in elite Norwegian team handball - Myklebust, G.; Maehlum, S.; Holm, I.; Bahr, R. (Scandinavian Journal of Medicine & Science in Sports, 1998)
The purpose of this study was to examine gender differences in the incidence of anterior cruciate ligament (ACL) injuries in a population of high-level team handball players. We also wanted to examine injury mechanisms and possible risk factors for ACL injuries, including menstrual status. The study was done prospectively during the 1993-94, 1994-95, and 1995-96 seasons. We found 28 ACL injuries, 23 among women (incidence: 0.31 +/- 0.06 injuries per 1000 player hours) and 5 among men (0.06 +/- 0.03 inj./1000 h; P < 0.001 vs women; risk ratio: 5.0). Of the 28 injuries, 24 occurred during competition (0.91 +/- 0.19 inj./1000 h; women: 1.60 +/- 0.35 inj./1000 h; men: 0.23 +/- 0.13 inj./1000 h; P < 0.001 vs. women; risk ratio: 7.0) and 4 during training (0.03 +/- 0.02 inj./1000 h; P < 0.001 vs. competition; risk ratio: 29.9). Nearly all the injuries (n = 25) occurred in non-contact situations when the players performed high-speed plant-and-cut movements which they were well accustomed to. A reliable menstrual history could be obtained in 17 of the 23 cases among females. Five of the injuries occurred in the menstrual phase, 2 in the follicular phase, 1 in the early luteal phase and 9 in the late luteal phase (chi-square3 d.f. = 13.2; P < 0.01). The results suggest that there may be an increased risk of ACL injury during the week prior to or after the start of the menstrual period.